2017
DOI: 10.1016/j.canlet.2016.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the apelin/apelin receptor axis decreases cholangiocarcinoma growth

Abstract: Purpose Cholangiocarcinoma (CCA) is a malignancy of the biliary epithelium that is associated with low five-year survival. The apelin receptor (APLNR), which is activated by the apelin peptide, has not been studied in CCA. The purpose of this study is to determine if inhibition of the apelin/APLNR axis can inhibit CCA growth. Methods Immunohistochemistry, rtPCR, immunofluorescence, flow cytometry, and ELISA was used to measure APLNR expression in human CCA cells and tissues. Mz-ChA-1 cells were treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 61 publications
1
42
0
Order By: Relevance
“…11 In a cholangiocarcinoma cell model and in in vitro/in vivo experiments with glioblastoma cells, inhibition of the APLN/APLNR axis has resulted in decreased proliferation and angiogenesis. 8,18 The role of the APLNR-axis for tumour neo-angiogenesis, especially under hypoxia, regulated by hypoxia-inducible factor (HIF)-1alpha, is well documented. 9,19,20 ccRCC is a highly vascularised tumour with high levels of intratumoural HIF, which accumulates due to inactivation of the von Hippel-Lindau gene.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…11 In a cholangiocarcinoma cell model and in in vitro/in vivo experiments with glioblastoma cells, inhibition of the APLN/APLNR axis has resulted in decreased proliferation and angiogenesis. 8,18 The role of the APLNR-axis for tumour neo-angiogenesis, especially under hypoxia, regulated by hypoxia-inducible factor (HIF)-1alpha, is well documented. 9,19,20 ccRCC is a highly vascularised tumour with high levels of intratumoural HIF, which accumulates due to inactivation of the von Hippel-Lindau gene.…”
Section: )mentioning
confidence: 99%
“…5 Since apelin (APLN) and the apelin receptor have long been known to play important roles in vascular physiology, 6,7 emerging evidence of their importance in oncological diseases is not surprising. [8][9][10][11] Given the paucity of data concerning the role of APLN and APLNR in renal cell carcinoma 12 and the importance of immune evasion mechanisms of this tumour, our study aimed to investigate the expression of APLN and APLNR in RCC and its association with clinicopathological parameters and survival.…”
Section: Introductionmentioning
confidence: 99%
“…APJ/apelin expression is elevated in many malignant tissues (4), indicating that its misexpression/activation may be crucial in tumorigenesis. Studies have also shown that increased expression and/or activation of this axis in the cancer cells as well as in the stroma, contributes to cancer progression mainly by increasing tumor-related angiogenesis (5-7) and proliferation (8)(9)(10). However, the extent of APJ expression by cancer cells and its pathophysiologic roles in human cancers remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that APLNR also plays an important role in tumors. Hall et al (15) reported that inhibition of APLNR decreases cholangiocarcinoma proliferation and angiogenesis, and overexpression of the apelin-APLNR axis induces tumor arteriogenesis in hepatocellular carcinoma (16).…”
mentioning
confidence: 99%